ANALISIS BESAR KECEPATAN GELOMBANG PRIMER PADA STASIUN BMKG WILAYAH IV MAKASSAR - Wahyuni, Ayusari; Ahmad, Nurul Fitriah; Nurhidayanti, Nurhidayanti; Astuti, Sri; Indah, Indah (JFT: Jurnal Fisika dan Terapannya, 2017)
Data analysis has been carried out to determine Primary wave velocity (Vp) using official data of the monthly report of Geophysics, Regional Earthquake Center (PGR) 4, Center for Meteorology Climatology and Geophysics (BMKG) region IV Makassar with seven stations namely BKSI (Bulukumba), SPSI (SPSI) Sidrap), KAPI (Kappang), PMSI (Majene), TTSI (Tana Toraja), LUWI (Luwuk Geofon Station, and MPSI (Mapaga). Based on data analysis, values of Vp ranged from 12.9105 km/s to 214437.1 km/s.